Possibilities of using Nicotiana species in breeding for virus resistance - Depta, Anna; Doroszewska, Teresa; Czubacka, Anna (Polish Journal of Agronomy, 2023)
Tobacco (Nicotiana tabacum L.) is an important industrial crop. Among the diseases causing losses in tobacco cultivation, viral ones are of particular importance due to the verylow effectiveness of chemical protection allowing only for vector control. The greatest threat to tobacco cultivation in Poland and in many countries of the world is posed by potato virus Y(PVY), tomato spotted wilt virus (TSWV) and, in recent years, the increasingly frequent tobacco mosaic virus (TMV). The geneticresources studies carried out in the genus Nicotiana haveshown a wide variation in species resistance, assessed biologically, serologically and molecularly, depending on the virus used and, in the case of PVY, also on the specific isolate. The results of the assessment of resistance in Nicotiana accessions presented in this paper, gathered from literature data as well as from our ownresearch, allow us to broaden and systematise our knowledge onthe sources of resistance to viral diseases. This is the only such anextensive study in this field. It provides an excellent information base for the appropriate selection of accessions for use in resistance breeding.